Aktivitas Magang Lembaga Keuangan Syariah dan Proyek Kemanusiaan dalam Kurikulum Merdeka Belajar Kampus Merdeka - M Makhrus; Safitri Mukarromah; Istianah Istianah; Restu Frida Utami (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2022)
The purpose of this study is to examine internship activities in Islamic financial institutions and humanitarian projects in improving the competence of graduates who have power in the world of work. This type of research is field research with research partners Bank Muamalat Purwokerto, KSU BMT Dana Mentari Purwokerto, and LAZISMU Banyumas Regency, while the data collection techniques are through observation, questionnaires, and interviews. This study indicates that the activities in the Independent Learning Campus (MBKM) curriculum of the Islamic Economics Law Study Program, Muhammadiyah University of Purwokerto have been going well and have had a positive impact on students and partners. Internships for Islamic financial institutions and humanitarian projects provide students with skills and competencies regarding product selling, product knowledge, communication skills, and humanitarian volunteer. Based on the evaluation results, students who take part in these two activities can increase motivation, skills, and behaviors that can affect future career plans (work) because they are in the world of work. In connection with efforts to increase graduate competence, it is carried out by increasing soft skills, namely by comprehensively understanding the entire series of internship activities for Islamic financial institutions and humanitarian projects, especially student activities that have met partner expectations, namely being diligent, communicative, active, and having competencies that are by partner needs.